A STUDY OF THE EFFECTIVENESS OF ACTION PROGRAMS FOR DISASTER MANAGEMENT AWARENESS OF STUDENT TEACHERS IN TEACHERS TRAINING COLLEGE - Raju Gulab Shaikh (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Disaster management is important in schools, for teachers and students. When it comes to safety, every school must consider that no disaster will happen. In order to create disaster awareness among school students, first of all teachers need to be literate or trained in disaster management. Mainly schools and teachers, students are an important resource for creating scope of disaster management awareness. In the background of this fact, the effectiveness of the action program has been studied for the knowledge of disaster management of the student teachers in the teachers’ school. An attempt has been made to find out the extent of disaster awareness among teacher trainees. A total of 200 student teachers of two teacher training schools in Sangamner, Ahmednagar district (Maharashtra) were selected to study disaster awareness through a survey and 100 students were studied on the effectiveness of disaster action program. It is clear from the results of the study that the awareness of the disaster and the effectiveness of the disaster action program are very positive.